Effect Of Inbreeding And Some Other Factors On Lactation Length In Malvi Cows - Sharma, Harish; Tomar , S.S.; Kumar, Amit (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The data for the present investigation pertained to 1647 observations of lactation length (LL) on Malvi cattle maintained at Govt. Cattle Breeding Farm, Agar, District Shajapur (M.P.), covering a period of 48 years from 1962 to 2009. The least squares analysis of variance revealed the mean lactation length in these cows to be 263.85±6.95 days and the trait was significantly affected by sire (P< 0.01), period of calving (P< 0.01), season of calving (P< 0.01) and parity of the cow (P< 0.01). Although, inbred cows had lower lactation length as compared to non-inbred cows, the effect of inbreeding was not significant. Heritability estimate for lactation length in the herd was obtained as 0.08±0.11. It was concluded that to improve the lactation length in this herd, ameliorative managerial practices should be adopted along with avoidance of inbreeding.
Keywords: Malvi cows; inbreeding; lactation length; heritability